Atraumatic splenic rupture with acute Varicella-Zoster infection (chickenpox) - M. A. Sayfullin; E. S. Makhinova; N. N. Zvereva; V. A. Morozov; E. A. Volobueva; A. A. Bogomolova; I. N. Tyurin (Журнал инфектологии)
Chickenpox, despite of introduction of vaccination, remains a common disease, mainly among children. In most cases, chickenpox is a self-limiting disease without the development of life-threatening conditions. The case of atraumatic splenic rupture associated with chickenpox is a too rare and we described seventh case over the past 55 years. The man was hospitalized in the infectious diseases hospital with a vesicular rash, abdominal pain and repeated vomiting with a referral diagnosis of “acute pancreatitis, chickenpox”. The diagnosis of chickenpox was confirmed (family contact, typical rash and IgM-VZV). Splenic rupture was described with computed tomography with a contrasting agent. Splenectomy performed in first day of hospitalization. Symptoms resolved against the background of antiviral therapy. There were no surgical complications.